The man and the lima bean (pallar) in the moche iconography - Hacquenghem, Anne-Marie (1984)
In an article entitled "Pythagore en Amérique", published in his book Le Regard Eloigne, Lévi-Strauss points out the particular place they attribute, to the seeds of the ancient family of legumes, peoples distant in time and space. This indicates us to return to the study of the pallares (lima beans) represented in the Moche iconography.